2014
DOI: 10.1161/circep.114.001568
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Ventricular Arrhythmia in Nonischemic Cardiomyopathy

Abstract: Background-The aim was to relate distinct scar distributions found in nonischemic cardiomyopathy with ventricular tachycardia (VT) morphology, late potential distribution, ablation strategy, and outcome. Methods and Results-Eighty-seven patients underwent catheter ablation for drug-refractory VT. Based on endocardial unipolar voltage, 44 were classified as predominantly anteroseptal and 43 as inferolateral. Anteroseptal patients more frequently fulfilled diagnostic criteria for dilated cardiomyopathy (64% vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 21 publications
4
111
0
Order By: Relevance
“…The Prospective Heart Centre of Leipzig VT study echoed that the long‐term outcomes in NICM patients were significantly worse than those in ICM patients (40% and 57% freedom from VT at 1‐year follow‐up for NICM and ICM patients, respectively),49 which was echoed by a substrate‐based approach 79. Additionally, patients with scar involving the inferolateral aspect of the LV, which frequently requires an epicardial approach, usually have a better prognosis than those with anteroseptal scar 80. The progressive disease entities and involvement of intramural and epicardial substrates might contribute to a worse prognosis in certain groups of patients.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…The Prospective Heart Centre of Leipzig VT study echoed that the long‐term outcomes in NICM patients were significantly worse than those in ICM patients (40% and 57% freedom from VT at 1‐year follow‐up for NICM and ICM patients, respectively),49 which was echoed by a substrate‐based approach 79. Additionally, patients with scar involving the inferolateral aspect of the LV, which frequently requires an epicardial approach, usually have a better prognosis than those with anteroseptal scar 80. The progressive disease entities and involvement of intramural and epicardial substrates might contribute to a worse prognosis in certain groups of patients.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…Epicardial mapping was not hampered by overlying structures like the left atrial appendage, a thick fat layer, or coronary arteries in these patients; however, radiofrequency delivery may need to be withheld if damage of the coronary arteries or the phrenic nerve cannot be excluded. Oloriz et al 26 confirmed subsequently these findings in a larger cohort of patients.…”
Section: Value Of the 12-lead Ecg To Predict The Underlying Substratementioning
confidence: 59%
“…If endocardial lesions are similar to the epicardial lesions demonstrated here, HIU ablation may also allow ablation of deep septal VTs, which are currently challenging to ablate using radiofrequency from either side of the interventricular septum. 20,21 In conclusion, we have developed an internally irrigated, side-facing, epicardial HIU catheter, capable of making large, deep lesions with sparing of epicardial tissue. Dose ranging studies showed that 20-W lesions had the best balance of depth of penetration and epicardial sparing.…”
Section: Discussionmentioning
confidence: 99%